Musculoskeletal sonography in the neonate and infant - Keller, Marc S. (Pediatric radiology, 2005)
Babies are ideal subjects for investigation by sonography. They are small and easily examined with the use of high-frequency transducers. Their unique status in US imaging tends to get lost amid the array of other available modalities, such as MRI and CT imaging. Some of the questions posed in pediatric musculoskeletal imaging that are routinely directed to other imaging modalities can be solved quickly at a lower cost by sonography in neonates and infants without sedation or any known clinical risk. These small children not only have thinner soft tissues but they have long bones and midline spine structures whose ends are largely composed of cartilage, which provides an early opportunity to examine these regions by US. And we cannot overestimate the value of new parents being able to stay next to their baby during imaging in a warm, friendly and non-threatening environment.